Kekerasan dalam Rumah Tangga Sebuah Kegagalan Penyelenggara Pendidikan dalam Pembelajaran Karakter Ketika di Sekolah Dasar - Supriatna, Hidayat; Hadi, Muhammad Sofian; Misriandi, Misriandi (ANWARUL, 2023)
Character education is very important for the student, it will take affect in the future including style in marriage. That’s the important point why this journal is born. Character education in primary schooll is very important for the student. It will take affect to the student in the hole his futures life. And then after we realize character education is important thing, we do must reform the curriculum of system educational especially about character education. We use mixed methods on our research journal. Kuantitatif methods mixed with kualitatif methods. In order to collection data sampling on this research we use two way data collection technique, participant observation both nonparticipant observation. We take sampling upto 10 family.The result of our research from 10 family is there isn’t value up to 60 percent. But all under 60 percent value neither each person get good character education or get a good methods character education when he in primary school. The conclution is domectic violence happening in a lot of amount in Indonesia is because this factor ; first is because the rolemodel of family arround his life is a bad rolemodel. Second is because when he in golden age years he doesn’t get a good character education or doesn’t get a creative teaching from his teacher so that cause he not get enough character education.